Morphological analysis and functional connectivity of the insular in patients with dysphagia after cerebral infarction based on resting-state fMRI - Ming Guo; Bingjie Li; Jun Zhao; Chen Bai; Weiyong Yu; Hongxia Zhang; Haoyuan Li; Yongxue Yuan; Qingsu Zhang; Tong Zhang (BMC Neurology)
Abstract Objective The insula, as a critical hub for multimodal information integration, plays a pivotal role in post-stroke dysphagia(PSD). However, the mechanisms underlying its structural and functional network reorganization remain elusive. This study aims to systematically investigate the alterations in gray matter volume and functional connectivity patterns of the insula in patients with dysphagia after cerebral infarction using multimodal neuroimaging techniques, and to untangle their clinical associations with swallowing function impairments. Methods Three groups of subjects were recruited: healthy controls (HC, n = 15), cerebral infarction patients without dysphagia (ND, n = 13), and cerebral infarction patients with dysphagia (DYS, n = 11). Resting-state functional magnetic resonance imaging (rs-fMRI) and high-resolution T1-weighted structural imaging data were acquired. Seed-based analysis (using the CONN FC toolbox) was employed to quantify the whole-brain functional connectivity (FC) of the insula, and voxel-based morphometry (VBM) was used to assess gray matter volume changes. Swallowing function was standardized using the Fiberoptic Endoscopic Evaluation of Swallowing (FEES) and the Penetration/Aspiration Scale (PAS). Results The DYS, ND, and HC groups showed significant differences in grey matter volume in the left insula (pFDR =0.041). Compared to the HC group, both cerebral infarction groups (ND and DYS) demonstrated increased functional connectivity between the left insula and the left lateral occipital cortex (superior division), left precuneus, and left cerebellum. In contrast, functional connectivity with the right insula cortex, right frontal operculum cortex, left anterior cingulate, and right frontal pole was decreased. Among these differences, compared to the ND group, the DYS group showed a more significant reduction in functional connectivity within the right frontal operculum cortex and a more pronounced increase in functional connectivity within the left lateral occipital cortex superior division and left cerebellum. Compared to the HC group, patients in both cerebral infarction groups (ND and DYS) showed significantly enhanced functional connectivity between the right insula and the right posterior cingulate gyrus, left lateral occipital cortex (superior division), right precuneus, left frontal pole and right frontal pole. Conversely, functional connectivity with the left insula cortex and left anterior cingulate gyrus was significantly reduced. Moreover, compared to the ND group, the DYS group demonstrated more pronounced increases in functional connectivity within the right posterior cingulate gyrus and right superior cerebellar peduncle, along with a more significant decrease in functional connectivity within the right insula cortex. Enhanced FC between the left insula and the left lateral occipital cortex (superior division) correlated positively with PAS, while enhanced FC between the right insula and the right cerebellum correlated negatively with PAS. Conclusion Our study found left insular gray matter atrophy underlies the pathology of PSD, and abnormal insular functional connectivity is key to its development. The severity of post-stroke dysphagia can affect the functional connectivity between the insula and the right cerebellum as well as the left occipital lobe. These results reveal potential neural compensation mechanisms in PSD and offer new directions for clinical prognostic biomarker development.